Transforming Education: The Impact of Transformational Leadership on Staff Performance - Soim, Soim (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2024)
This study aimed to examine and analyze the relationship between the variables of idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration on the performance of educational staff. This study used a quantitative and explanatory approach through a survey technique. The questionnaire was compiled based on the research variables, namely transformational leadership and educational staff performance. Because the exact population size is unknown, the sample size was calculated using the Cochran formula. Data were collected from 100 educational staff members who were the sample of this study. Data analysis was carried out using multiple regression analysis and the Sobel test. The results of the study showed that idealized influence had a positive and significant effect on the performance of educational staff; inspirational motivation had a positive and significant effect on the performance of educational staff; intellectual stimulation had a positive and significant effect on the performance of educational staff; and individualized consideration had a positive and significant effect on the performance of educational staff. Leaders and management can utilize this study's results to improve educational staff performance. The variables that affect the performance of educational staff can be used as targets for change to improve performance.